Effectiveness of the classroom communication resource in changing primary school learners' attitudes towards children who stutter after one month: A feasibility study - Walters, Freda Aletta (Division of Communication Sciences and Disorders, 2015)
Children who stutter are bullied and teased by their peers, especially in the primary schooling years. The Classroom Communication resource (CCR) was developed as a teacher-administered classroom-based education programme aiming to improve peers' attitudes towards CWS. The focus of this feasibility study was to determine the initial treatment effect of the CCR to improve peers' attitudes towards CWS and the feasibility for a larger scale cluster randomised trial (CRT) in future. Peer attitudes were determined via a Likert scale questionnaire, the Stuttering Resource Outcomes Measure (SROM), completed by primary school learners. Aim one was to establish if the SROM was a valid and reliable outcomes measure. Aim two utilized a quantitative, CRT design with a control group to describe the direction and magnitude of changes in 196 Grade 7 peers' attitudes towards CWS following the administration of the CCR. It also determined whether the changes were linked to gender or having exposure to a person who stutters. The evidence confirmed that the SROM was a valid and reliable outcomes measure. Attitude changes after the administration of the CCR were analysed through inferential statistics. A significant positive change in SROM scores was found in the experimental group (p=0.005) when compared to the control group (p=0.41). Females had a greater magnitude of change in SROM scores after the administration of the CCR compared to males. Participants with prior exposure to a person who stutters held more positive attitudes towards CWS at pre-test. The magnitude of positive change in SROM was greater in participants who did not have prior exposure to a person who stutters (p=0.007). The study indicated initial positive treatment effect of the CCR and implications for the feasibility of a larger CRT is discussed.